A Comparative Analysis of Anuerysmal Subarachnoid Hemorrhage by Computed Tomographic Angiography versus Digital Subtraction Angiography - Mehmood, Atif; Mehmood, Kashif (Annals of Allied Health Sciences, 2017)
Introduction: Rupture of intracranial aneurysms and distortions are the major reasons for unconstrained subarachnoid hemorrhage (SAH). The objective of this study was to determine the effectiveness of Computed Tomographic Angiography (CTA) for the diagnosis of cerebral aneurysms in patients with non-traumatic SAH in comparison to intra-blood vessel Digital Subtraction Angiography (DSA). Methods: In this cross sectional diagnostic relative study, DSA and CTA were compared. Sensitivity and specificity of the two diagnostic modalities were computed. From crude information, three dimensional volume rendered recreation and two dimensional greatest power projection (MIP) perspectives were finished. The morphologic Information of aneurysm on CTA was contrasted with DSA, which is considered the best quality level imaging technique. Results: Out of 70 patients, cerebral CTA analyzed intracranial aneurysms in 67 patients.Study of DSA affirmed the vicinity of intracranial aneurysms in 90 patients (n=63). While diagnosing cerebral aneurysms, The study discovered that the sensitivity of CTA was 97% and the specificity was 100%. Conclusions: According to our study, cerebral CTA is more sensitive, non invasive and quick imaging strategy than DSA in the evaluation of cerebral aneurysms in patients havingSAH